NoSql Database Modeling Techniques and Fast Search of Enterprise Data - Thaduri, Upendar Rao; Lal, Karu (Engineering International, 2022)
There is a need for quick databases that can deal with enormous amounts of data because of the rapid growth of the Internet and the increase in the number of websites that allow users to develop their material, such as Facebook and Twitter. To accomplish this goal, new database management systems, which will be referred to collectively as NoSQL, are currently under development. Because there are various NoSQL databases, each with unique performance, it is essential to evaluate database performance. MongoDB, Cassandra, and Couchbase are the names of the three significant NoSQL databases considered for the performance evaluation. To investigate performance, a variety of workloads were developed. The read and update operations served as the basis for the evaluation that was carried out. The results of this study provide the ability to select the NoSQL database that best meets their requirements in terms of the particular mechanisms and applications.